## Algebra Formulas:

(a + b)^{2} = a^{2} + b^{2} + 2ab |

(a – b)^{2} = a^{2} + b^{2} – 2ab |

a^{2} – b^{2} = (a + b) (a – b) |

a^{2} + b^{2} = (a + b)^{2} – 2ab or (a – b)^{2} + 2ab |

(a + b)^{2} + (a – b)^{2} = 2 (a^{2} + b^{2}) |

(a + b)^{2} – (a – b)^{2} = 4ab |

(a + b)^{3} = a^{3} + b^{3} + 3ab (a + b) |

(a – b)^{3} = a^{3} – b^{3} – 3ab (a – b) |

a^{3} + b^{3} = (a + b) (a^{2} – ab + b^{2}) |

a^{3} – b^{3} = (a – b) (a^{2} + ab + b^{2}) |

(a + b + c)^{2} = a^{2} + b^{2} + c^{2} + 2ab + 2bc + 2ca |

(a – b – c)^{2} = a^{2} + b^{2} + c^{2} – 2ab + 2bc – 2ca |

a + b + c = (a^{3} + b^{3} + c^{3} – 3abc) / (a^{2} + b^{2} + c^{2} – ab – bc – ca) |

If a + b + c = 0, then a^{3} + b^{3} + c^{3} = 3abc |